Impact of Crop Residue Burning on Soil Properties, Microbial Activity, and CO2 Emissions - Wena Shafeeq Tawfeeq; Hastyar Hama Rashid Najmuldeen; Mohammed Hassan; Hassan Hussein Hama Amin; Ghafoor Ahmed Mam Rasul (Applied and Environmental Soil Science)
Crop residue burning, a common agricultural practice in wheat cultivation, has significant implications for soil health, nutrient cycling, and microbial communities. This study evaluates the effects of residue burning on soil physicochemical properties, microbial populations, and CO2 emissions in wheat fields across Wazha village and Sitak, Sulaymaniyah Province, Kurdistan, Iraq. Post-burning analysis revealed a consistent shift in soil texture from silty clay loam to clay loam due to reduced silt content. Soil organic matter significantly declined from 15.63 ± 0.87 to 11.78 ± 0.28 g/kg (p≤0.05), alongside a marked decrease in magnesium concentration from 0.18 ± 0.02 to 0.06 ± 0.02 mmol/L (p≤0.05). In contrast, other parameters such as pH, electrical conductivity, calcium, potassium, and nitrogen remained largely unaffected. Microbial populations, including bacteria, fungi, and actinomycetes, exhibited resilience, showing no significant changes in abundance. CO2 emissions demonstrated an initial rapid release of CO2-C due to microbial degradation of organic matter, followed by a slower mineralization rate over time. These findings highlight the detrimental impact of crop residue burning on essential soil properties, particularly organic matter and magnesium, which are critical for maintaining soil fertility. The study emphasizes the need for sustainable agricultural practices to mitigate the negative effects of residue burning, enhance soil health, and support long-term agricultural productivity.